Online social networking and its relationship with mental health and emotional intelligence among female students - Tenzit Tyagi; Santosh Meena (Elsevier, 2022)
Over the past two decades, online social networking (OSN) is serving as a ubiquitous means of communication. The main objective behind this research is to discover the relationship between online social networking and mental health, emotional intelligence, respectively. Pearson's correlation coefficient is applied as multi-variate analysis, to assess the association between OSN, mental health and emotional intelligence. The negative correlations between OSN and mental health (−0.133) and OSN and emotional intelligence (−0.198) suggest that excessive use of OSN is detrimental to mental health and emotional intelligence. The study found that comparatively younger children have higher practice of OSN and so having lower emotional intelligence than the older ones. But in case of Mental health, relatively, older female adolescents have experienced the mental health problems. Present study concluded that there is significant relationship between online social networking, mental health and Emotional intelligence.